Proximate and Mineral Elements Composition of Water Soaked Carnavalia ensiformis Seeds - Akingbade, A.A.; Sodeinde, F.G.; Olaniyi, C.O.; Oyetayo, T.S.; Fadare, O.R.; Rabiu, A.O. (Pakistan Journal of Nutrition, 2009)
The study examines the proximate and mineral elements constituents of water soaked Jack Bean (Carnavalia ensiformis) seeds. The seeds were subjected to four treatments which comprised: 24 hrs, 48 hrs, 72 hrs and 96 hrs soaking in cold water with each treatment made up of three replicates. After the expiration of each soaking period, the water was discarded, sun-dried for 7 days and thereafter milled to pass through 1 mm sieve and subjected to laboratory analysis. The study revealed the following: dry matter increased after 96 hrs of soaking. Crude protein (CP) however decreased in value from 21% to 17%. Soaking for 48 hrs led to a reduction in the crude fibre (CF) content of seeds. Prolonged soaking period of 96 hrs increased the ether extract (EE) level. However, total ash content was reduced in seeds soaked for 96 hrs soaking. Soaking for 96 hrs increased Mg, Fe and Cu contents but Zn content recorded a decrease. Differences between treatments for all the parameters considered in the study were significant (P < 0.01).